Revenge, resurrection and redemption: Mapping the mystiques of mimesis in Stieg Larsson’s The Girl with the Dragon Tattoo - Padgate, Usa (Humanities, Arts and Social Sciences Studies, 2022)
This study investigates the phenomena of mystique in Stieg Larsson’s crime novel The Girl with the Dragon Tattoo. The objectives of the study are twofold: to illustrate how mystique often leads to acts of mimicry, and to map the mimesis inspired by the mystique of the novel’s central crime investigation to reflect on religious references based on René Girard’s mimetic theory. The analysis is presented in two parts. The first part traces how elements of mystique such as the mystery of an impossible crime and the allure of divine legitimacy create both personal obsession and cultural fanatism displayed through imitative actions of various key characters. The second part applies René Girard’s triangle of desire to illustrate how mimetic desire can bring about a sense of rivalry that triggers a chain of violent actions, which entails casualties both intentional and accidental. The analysis also applies Girard’s scapegoat mechanism to reveal how the narrative rids itself of violence and resumes its status quo through sacrificing the social ties between the male and female protagonists. The study concludes by projecting that the novel itself is fashioned in imitation of the Christian belief and that the storylines involving the key players in the triangle of desire are marked by the Christian themes of revenge, resurrection and redemption. This suggests that mimesis directs the plot and motivates the players, and that cultural ideologies, such as a major world religion, are indeed too potent and irresistible not to mimic, even for an author who has set out to caution his readers against the risk of mimicking.